2012
DOI: 10.1177/1359104512458204
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in foster and kinship care: A systematic review

Abstract: Foster care is a complex setting in which to provide therapeutic interventions due to the high rates of difficulty, poor outcomes and high numbers of professionals and carers involved. This systematic review aims to examine interventions that have been empirically assessed in foster care. Thirty papers describing 20 interventions were included. It was found that there was good support for wraparound services and relational interventions, but little support for widely used carer training programmes. A need was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 68 publications
(413 reference statements)
0
46
0
Order By: Relevance
“…Most notable was their frustration with behavioral approaches, which seemed to further repel children from forming a loving relationship with their adoptive parents. This finding underscores the results of studies (Kinsey & Schlösser, ; Purvis et al, ) that found that behavioral interventions were not strongly supported for application with traumatized children. Researchers have discovered that traumatized children frequently exhibit elevated cortisol levels associated with posttraumatic stress disorder that can entrap them in a chronic state of flight, fight, or freeze (Carnes‐Holt & Bratton, ).…”
Section: Discussionmentioning
confidence: 53%
“…Most notable was their frustration with behavioral approaches, which seemed to further repel children from forming a loving relationship with their adoptive parents. This finding underscores the results of studies (Kinsey & Schlösser, ; Purvis et al, ) that found that behavioral interventions were not strongly supported for application with traumatized children. Researchers have discovered that traumatized children frequently exhibit elevated cortisol levels associated with posttraumatic stress disorder that can entrap them in a chronic state of flight, fight, or freeze (Carnes‐Holt & Bratton, ).…”
Section: Discussionmentioning
confidence: 53%
“…The reviews of studies of training programs, most of which were systematic reviews, reported limitations in the methodologies of studies, which in turn limited generalisable conclusions. In summary, standalone training was generally not supported by the evidence in terms of child outcomes or placement stability (Everson-Hock et al, 2012;Kinsey & Schlösser, 2012). Multi-session programs of longer durations (10-16 weeks) had more beneficial effects than single sessions (Everson-Hock et al, 2012;Festinger & Baker, 2013).…”
Section: Evidence On Training Of Carersmentioning
confidence: 92%
“…6. Training programs which show the greatest promise in USA research reviews are those which give the opportunity for foster carers to practise new learning in their own homes with their child in care, as well as to receive feedback on this, such as Multidimensional Treatment Foster Care derivatives such as KEEP (Keeping Foster and Kin Parents Trained and Supported) (Kinsey & Schlösser, 2012;Leve et al, 2012).…”
Section: Support and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children in foster care are more likely to experience disruptions in brain and neurobiological development, stress-response systems and executive functioning due to early experiences of neglect, abuse and/or abandonment, or prenatal exposure to alcohol and drugs; this in turn may negatively impact the child's development, behaviour and ability to form social relationships (LEVE et al, 2012). For these reasons, many caregivers find caring for a child/adolescent in foster care to be challenging and stressful (DORSEY et al, 2008;EVERSON-HOCK et al, 2012;KINSEY;SCHLÖSSER, 2013;TURNER et al, 2007). Without more explicit guidance how best to meet the complex needs of children/adolescents in alternative care in ways that promote resilience and growth, caregivers may not only exacerbate any difficulties the children/adolescents experience but also inadvertently replicate the very social power relationships that fuel the cycle of social inequality (LUVIZARO; GALHEIGO, 2011).…”
Section: Introductionmentioning
confidence: 99%